Epilogue: A New Paradigm for the Science and Practice of Engaging Young People. Issue 13 (April 2014) - Larson, Reed W.; Shernoff, David J.; Bempechat, Janine
A hope of this Yearbook is to illuminate not only what promotes engagement but also how it can be fostered. In this epilogue, first we provide a short history of research on motivation. We then review the contributions of this Yearbook in providing a fuller, multidimensional, contextualized picture of human motivation, one that we believe is relevant and helpful to educational policy and practice. Last, we discuss where this research may head in order to engender conditions in which engagement in schooling becomes more universal.